THE INFLUENCE OF CASHIER SYSTEM DEVELOPMENT TRAINING USING PYTHON IPYWIDGETS ON BASIC PROGRAMMING SKILLS - Septiandi Putra; Muammar Revnu Ohara; Vebby Vebby (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study aims to analyze the effect of cashier system development training using Python Ipywidgets on the basic programming skills of students at SMA PGRI Pekanbaru. A quantitative approach was applied using a pre-experimental one-group pretest-posttest design. The sample consisted of 40 students who completed the training and both pre-test and post-test sessions. The research instrument was a multiple-choice test based on core programming competency indicators. Results showed an increase in the average score from 46.75% to 64.63%, with a gain of 17.88%. Inferential statistical analysis using a paired sample t-test confirmed a statistically significant improvement (p < 0.05). These findings indicate that real project-based training supported by interactive media such as Ipywidgets effectively enhances students’ understanding of fundamental programming concepts and strengthens digital literacy at the secondary school level.